ʻAlāqah al-Khalfiyyat at-Taʻlīmiyyah al-Lugah al-ʻArabiyyah ʻalā Mahārah al-Qirā’ah - Solehuddin Solehuddin; Muhammad Arif Setiabudi (INAIFAS PRESS, 2021)
Arabic language education background has an important relationship with students' reading skills, however the situation in each place of learning is different, where public schools do not teach Arabic, while Islamic religious-based schools are the opposite. This article aimed to find 1) the educational background of students; 2) students' reading skills; and 3) the relationship between educational background and reading skills. Researchers used quantitative methods with the research subjects of seventh grade students of MTs Salafiyah Syafi'iyah Seblak Jombang. The results of the research showed 1) the educational background of the percentage of students who voted strongly agree 40%, 43% agree, 15% disagree, and 2% strongly disagree; 2) the students' ability to read Arabic at a very good level of 53.57%, good 33.92%, and not good 14.28%; and 3) there were a relationship between educational background and reading ability of students based on the value of Sig2 tailed = 0.466 which is greater than 0.05. This shows that Islamic religious-based schools encourage students to have Arabic reading skills.